Intrathyroidal cytokine gene expression in Hashimoto's thyroiditis - AJJAN, R A (Blackwell Science Inc, 1996)
Hashimoto's thyroiditis (HT) is an organ-specific autoimmune disease in which cytokines are likely to have a role in the initiation and perpetuation of the disease. Using the reverse transcription-polymerase chain reaction (RT-PCR) we analysed the cytokine profile in four HT tissue samples. Furthermore, cell fractionation was carried out on two tissue samples and cytokine profile was studied in CD4(+) and CD8(+) T cells, in addition to the residual cellular infiltrate composed of CD4(−) and CD8(−) cells. Our results showed IL-1β, IL-4 and IL-6 mRNA expression in three out of four tissue samples, whereas IL-1α, IL-2, IL-8, IL-10, interferon-gamma (IFN-γ) and tumour necrosis factor-alpha (TNF-α) were expressed in all tissue samples studied. Expression of IL-1α and IL-1β was absent in both CD4(+) and CD8(+) subsets. However, IL-2, IL-4, IL-6, IL-8, IFN-γ and TNF-α mRNA were detected in both CD4(+) and CD8(+) subsets. IL-10 was expressed in the CD4(+) subset in one sample, whereas it was negative in both CD8(+) fractions. All the cytokines studied were expressed in the residual infiltrate. These results suggest a mixed Th1 and Th2 response in HT, both of which may have an important role in the pathophysiology of the thyroid destructive process through cell-mediated cytotoxicity, and/or humoral autoimmunity manifested by autoantibody production.